2016
DOI: 10.1111/jam.13093
|View full text |Cite
|
Sign up to set email alerts
|

Study of silver nanoparticles synthesized by acidophilic strain of Actinobacteria isolated from the of Picea sitchensis forest soil

Abstract: The synthesized silver bionanoparticles from Streptacidiphilus sp. strain CGG11n possess potent inhibitory effect that offers valuable contribution to pharmaceutical associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…According to Railean‐Plugaru et al. CGG silver nanoparticles are stable at pH 6–8 range. We excluded the possibility of antibiotic precipitation at these values of pH.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Railean‐Plugaru et al. CGG silver nanoparticles are stable at pH 6–8 range. We excluded the possibility of antibiotic precipitation at these values of pH.…”
Section: Resultsmentioning
confidence: 97%
“… confirmed the synergistic antibacterial effect of β‐lactam antibiotics and chemically synthesized silver nanoparticles against E. coli . Moreover, research on biologically synthesized silver nanoparticles suggest that their antibacterial activity is increased when are applied in combination with antibiotics, such as ampicillin, streptomycin, gentamicin, vancomycin, and kanamycin . In our previous study on biologically synthesized silver nanoparticles functionalized with tetracycline we have also shown that such combination increased antimicrobial activity relative to S. aureus , P. aeruginosa , K. pneumoniae , S. epidermidis , and E. coli .…”
Section: Introductionmentioning
confidence: 93%
“…Hence, bacteria suspended in NaCl showed greater dispersion stability. This phenomenon is caused by repulsive forces between solvated biocolloids of bacterial cells generated by sodium ions [51, 53]. Potassium ions have a greater ionic radius than sodium ions, which reduces the shielding effect between biocolloids [54].…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing influence of pH of the system a sharp decrease of zeta potential was noticed for pH 2–4 which was a result of progressive deprotonation of carboxyl groups of bacterial structural components. For pH 5–8 a constant value of zeta potential could be observed which reflected the proteolytic balance [53, 55]. Bacteria after biosorption of Ag + show higher electric charge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation